Tailwind CSS from scratch learn by building projects (Packt Publishing, 2022)
Learn to build five mini projects and six website projects and become an expert by taking up the course. About This Video Learn the Tailwind utility classes using a code sandbox Learn how to set up a dev environment using the Tailwind CLI Learn to build five mini-projects and six website projects In Detail We will start with coding Sandbox and explore pages/videos for colors, typography, spacing, flex classes, and much more. This allows us to touch on all parts of Tailwind in a specific order, rather than just jumping right into projects. We will take what we learn in the Sandbox environment and use it to create some small projects. Next, we will start to work on larger landing-page websites. There will be six different websites. They are all very modern and clean looking. We partnered with Frontend Mentor for the designs. Some projects will have a bit of JavaScript for things such as hamburger menus, tabs, and some validation. Let us look at the projects: -Clipboard Website: Simple software product landing page focusing on Flexbox and alignment. -Loopstudios: VR company website with cool images, responsive mobile menu with some JavaScript, gradient overlay effects. -Shortly: Responsive menu and a little JavaScript for some form validation and working with the DOM. -Testimonial Grid: A project where we focus on using Tailwind's grid classes. -Fylo: Product page with a light/dark mode feature. We will add some JavaScript to save the color mode to local storage. We will also have a dynamic tab component for the FAQ. Bookmark: Bookmark manager extension landing page. This website will have some dynamic background images, a hamburger menu, and some tabs that will use JavaScript. By the end of this course, you will efficiently use Tailwind CSS utility classes. Audience This course has been designed for anyone that wants to get better at creating websites and UI layouts. A basic understanding of CSS grids, layouts, and JavaScript will be an advantage.